Effective microorganism solution-imbued sustainable self-curing concrete: Evaluation of sorptivity, drying shrinkage and expansion - Huseien G.F.; Memon R.P.; Baghban M.H.; Faridmehr I.; Wong L.S. (Elsevier Ltd, 2025)
Production of various concrete elements at early ages requires careful water curing to ensure the development of a hydration reaction that fills and discontinues the capillary voids, thus achieving the desired strength of the hydrated products. In real practice, problems occur where appropriate curing is tricky to attain targeted structural components like inclined, high-rise, and thick concrete elements. To meet this goal, this study evaluated the engineering properties of some newly designed concrete incorporated with effective microorganism (EM) solutions as new self-curing agents at varying contents (5, 10, 15, 20, and 25% in place of water). The casted specimens were subjected to wet and dry curing regimes. The effects of EM solutions at various contents on the strength development, sorptivity, drying shrinkage, expansion, and microstructures of the proposed concrete were determined. The results indicated that the specimens containing 10% of EM (optimum) as water replacement achieved the highest strength (48.9 MPa) at 28 days of curing. Compared to the control sample, the permeability, drying shrinkage, and expansion of the specimen made with 10% of EM were correspondingly reduced by 2.5%, 48%, and 49%. In addition, the optimum sample displayed denser texture and gel formation with fewer voids than other specimens. The optimum specimen exhibited nearly 12% more hydration than normal concrete in water curing. It was established that an EM solution in place of water in concrete can serve as an effective self-curing agent for the sustainable growth of high-performance construction materials. ? 2024